UNRAVELING ENGLISH FOR SPECIFIC PURPOSES NEEDS IN AUTOMOTIVE ENGINEERING EDUCATION - Effendi, Muhammad Idris; Nurjanah, Lailatul; Wicaksono, Bayu Hendro (Universitas Negeri Malang, 2023)
The disparity between Engineering Education and the imperative for English language proficiency remains significant. Frequently, engineering students exhibit a deficiency in practical English skills, particularly in English for Specific Purposes (ESP), a necessity for their forthcoming careers or advanced pursuits. In response to this challenge, this study seeks to carry out a need analysis of the English language within the domain of Automotive Engineering Education. Executed as a literature review, the study meticulously examines pertinent journals and scholarly texts on ESP. Additionally, it incorporates interviews with English language professors at the tertiary level to ascertain appropriate English language content suitable for inclusion in Automotive Engineering Education curricula. By drawing upon the analytical framework of Basturkmen and Dudley-Evans' Need Analysis, in conjunction with the methodology of St John & Saint John, the research delineates and assesses these identified needs within the context of Automotive Engineering Education programs. The investigation discerns the specific language components pivotal for facilitating effective communication within the sphere of Automotive Engineering Education